2021
DOI: 10.3390/ma14247527
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Relaxation of OSB Beams Reinforced with CFRP Composites

Abstract: An experimental and analytical approach to the relaxation problem of wood-based materials—OSB (Oriented Strand Boards—pressed wood-based composite panels) beams, including beams with CFRP (Carbon fiber reinforced polymer) tape composite reinforcement, is presented. It is a relevant engineering and scientific problem due to the fact that wood and wood-based materials, as well as composite reinforcements, are widely used in building constructions. Their rheological properties are very important and complicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The results showed that the proposed reinforcement solution was profitable on account of the strength, stiffness, and construction safety. Socha et al [120] introduced an experimental and analytical approach to the relaxation problem of the beams made of wood-like materials (Oriented Strand Boards-pressed wood-based composite panels), also the beams reinforced with CFRP tape. Rheological properties of such composites are important and difficult to estimate.…”
Section: Cfrp + Woodmentioning
confidence: 99%
“…The results showed that the proposed reinforcement solution was profitable on account of the strength, stiffness, and construction safety. Socha et al [120] introduced an experimental and analytical approach to the relaxation problem of the beams made of wood-like materials (Oriented Strand Boards-pressed wood-based composite panels), also the beams reinforced with CFRP tape. Rheological properties of such composites are important and difficult to estimate.…”
Section: Cfrp + Woodmentioning
confidence: 99%
“…Numerous numerical investigations were conducted to assess the efficacy of a boron/ epoxy repair (Salem et al, 2018(Salem et al, , 2021Serier et al, 2016;Ru zek et al, 2015;Makwana and Shaikh, 2019;Socha et al, 2021;Rabczuk et al, 2008). The endurance and trustworthiness of structures repaired with composite patches primarily hinge on the mechanical and thermal characteristics of the adhesive layer, constituting critical elements in the examination of failure causes and the deterioration of the entire repair process (Ufklyh et al, 2019;Yu et al, 2021;Zhuang and Talreja, 2014;Rabczuk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kawecki and Podgórski [ 20 ] conducted experimental, theoretical and numerical studies on glue laminated timber beams strengthened with the CFRP laminates—proving the necessity of including cohesive stiffness of the adhesive layers in the evaluation of the stiffness of the composite wood–CFRP. Rheological relaxation of OSB (Oriented Strand Boards) beams reinforced with CFRP tape was investigated by Socha et al [ 21 ]. Authors achieved a 63% improvement of stiffness and higher carrying capacity for reinforced beams in comparison to beams without reinforcement.…”
Section: Introductionmentioning
confidence: 99%